Poorer sustained attention in bipolar I than bipolar II disorder - Kung, Chian-Huei (BioMed Central, 2010)
BACKGROUND: Nearly all information processing during cognitive processing takes place during periods of sustained attention. Sustained attention deficit is among the most commonly reported impairments in bipolar disorder (BP). The majority of previous studies have only focused on bipolar I disorder (BP I), owing to underdiagnosis or misdiagnosis of bipolar II disorder (BP II). With the refinement of the bipolar spectrum paradigm, the goal of this study was to compare the sustained attention of interepisode patients with BP I to those with BP II. METHODS: In all, 51 interepisode BP patients (22 with BP I and 29 with BP II) and 20 healthy controls participated in this study. The severity of psychiatric symptoms was assessed by the 17-item Hamilton Depression Rating Scale and the Young Mania Rating Scale. All participants undertook Conners' Continuous Performance Test II (CPT-II) to evaluate sustained attention. RESULTS: After controlling for the severity of symptoms, age and years of education, BP I patients had a significantly longer reaction times (F((2,68) )= 7.648, P = 0.001), worse detectability (d') values (F((2,68) )= 6.313, P = 0.003) and more commission errors (F((2,68) )= 6.182, P = 0.004) than BP II patients and healthy controls. BP II patients and controls scored significantly higher than BP I patients for d' (F = 6.313, P = 0.003). No significant difference was found among the three groups in omission errors and no significant correlations were observed between CPT-II performance and clinical characteristics in the three groups. CONCLUSIONS: These findings suggested that impairments in sustained attention might be more representative of BP I than BP II after controlling for the severity of symptoms, age, years of education and reaction time on the attentional test. A longitudinal follow-up study design with a larger sample size might be needed to provide more information on chronological sustained attention deficit in BP patients, and to illustrate clearer differentiations between the three groups.